Knowledge brokers or relationship brokers? The role of an embedded knowledge mobilisation team. (10th May 2018) - Wye, Lesley; Cramer, Helen; Carey, Jude; Anthwal, Rachel; Rooney, James; Robinson, Rebecca; Beckett, Kate; Farr, Michelle; le May, Andrée; Baxter, Helen
Abstract : Aim: Policymaking decisions are often uninformed by research and research is rarely influenced by policymakers. To bridge this 'know-do' gap, a boundary-spanning knowledge mobilisation (KM) team was created by embedding researchers-in-residence and local policymakers into each other's organisations. Through increasing the two-way flow of knowledge via social contact, KM team members fostered collaborations and the sharing of 'mindlines', aiming to generate more relevant research bids and research-informed decision-making. This paper describes the activities of the KM team, types of knowledge and how that knowledge was exchanged to influence mindlines.Discussion: KM team activities were classified into: relational, dissemination, transferable skills, evaluation, research and awareness raising. Knowledge available included: profession-specific (for example, research methods, healthcare landscape), insider (for example, relational, organisation and experiential) and KM theory and practice. KM team members brokered relationships through conversations interweaving different types of knowledge, particularly organisational and relational. Academics were interested in policymakers' knowledge of healthcare policy and the commissioning landscape. More than research results, policymakers valued researchers' methodological knowledge. Both groups appreciated each other as 'critical friends'.Conclusion: To increase research impact, 'expertise into practice' could be leveraged, specifically researchers' critical thinking and research methodology skills. As policymakers' expertise into practice also bridges the know-do gap, future impact models could focus less on evidence into practice and more on fostering this mutual flow of expertise. Embedded knowledge brokers from the two communities working in teams can influence the mindlines of both. These ambassadors can create improvements in 'inter-cultural competence' to draw academia and policymaking closer.